The harm susceptibility model: a method to prioritise risks identified in patient safety reporting systems. Issue 5 (28th April 2010) - Pham, Julius Cuong; Colantuoni, Elizabeth; Dominici, Francesca; Shore, Andrew; Macrae, Carl; Scobie, Sara; Fletcher, Martin; Cleary, Kevin; Goeschel, Christine A; Pronovost, Peter J
Abstract : Background: Medical errors are endemic in healthcare. Patient safety reporting systems (PSRSs) have been developed and implemented to identify and reduce medical errors. Although they have succeeded in identifying errors (over 1 million reports in the NHS), there are limited methods by which to analyse this large number of events. Methods: Adapting the safety theory of risk resiliency, the authors developed the Harm Susceptibility Model (HSM) as a method of quantifying the variation in risk of harm within an organisation and the Harm Susceptibility Ratio (HSR) as a statistic to compare and rank harm across trusts or work areas. The HSM was applied to data from 20 trusts reporting events to the National Reporting and Learning System (NRLS) between 2004 and 2006. Findings: A total of 104 674 incident reports from 12 distinct work areas were analysed. Fifty-five per cent of the variation in harm was attributed to differences among trusts, suggesting that HSR would best be used within trusts. Within a specific trust, the HSR ranged from 0.25 to 4.30, with the pharmacy having the highest HSR (4.30, 1.89 to 9.68). The A&E, therapy department and radiology had the highest probability of a high HSR across the majority of trusts. Interpretation: The HSM can be used to analyse a large number of incident reports from PSRSs. It provides a quantifiable way for organisations to identify areas where defences against errors are weak and prioritise limited resources directed at improving patient safety.